The relationship between digital resource allocation and digital literacy of kindergarten teachers: the chain mediating effect of self-efficacy and learning motivation - He, Fei; Wen, Liying (Frontiers in Psychology, 2025)
IntroductionResearch on digital literacy has become deeply integrated into the field of teacher education, significantly influencing educational practices, including kindergarten education. For kindergarten teachers, possessing adequate digital literacy is essential for effectively conducting teaching activities and improving overall work efficiency. However, existing studies on digital literacy primarily focus on assessing individual teacher competency levels or conducting macro-level analyses of national policies.MethodsThis study examines the correlation mechanism between digital resource allocation and the digital literacy of kindergarten teachers. The research sample includes 317 kindergarten teachers from southeastern China. Data were analyzed using SPSS 29.0 and Mplus 8.0.ResultsThe results reveal that digital resource allocation is significantly and positively correlated with kindergarten teachers’ digital literacy. Moreover, both self-efficacy and learning motivation serve as mediating factors in this relationship. Notably, self-efficacy and learning motivation also form a chain mediation effect between digital resource allocation and digital literacy. Additionally, the direct effects of these factors on digital literacy, while present, are not significant.DiscussionThese findings underscore the importance of digital resource allocation, self-efficacy, and learning motivation in enhancing digital literacy among kindergarten teachers. The study provides valuable insights for developing strategies to support and improve digital literacy in kindergarten teachers.